Topographical and biometrical anatomy of the digestive tract of White New Zealand Rabbit (Oryctolagus cuniculus) - Nath, Sabuj Kanti; Das, Sujan; Kar, ]otan; Afrin, Khurshida; Dash, Amith Kumar; Akter, Sharmin (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: This study was constructed to build up the normal dimensions of the digestive tract of domestic Rabbit (Oryctolagus cuniculus). Materials and methods: Five rabbits of both sexes were used in this study. After dissection of the rabbits, the exact positions of different parts of the digestive tract (i.e., esophagus, stomach, small intestine, large intestine) were measured using Metric rule, thread, electronic and normal balance. Results: The mean lengths of the small intestine and large intestine were 169.53±21.65 and 132.3±17.42 cm, respectively, and weight of the whole digestive tract was 263.60±56.80 gm. The mean lengths and mean diameter of esophagus, duodenum, jejunum, ileum, cecum, colon and rectum were 9.62±1.64, 41.26±4.06, 106.60±14.64, 21.64±46.32, 41.14±2.82, 83.16±13.74 and 8.0±1.08 cm and 1.16±0.12, 1.71±0.11, 1.70±0.09, 1.73±0.05, 5.47±0.15, 3.36±0.16 and 2.81±0.24 cm, respectively. Conclusion: These results can be considered as a baseline study that may assist in disease diagnosis and clinical works with rabbits. http://doi.org/10.5455/javar.2016.c144